Rotational thromboelastometry along with thromboelastography plays a critical role in the management of traumatic bleeding - Durila, Miroslav; Malošek, Martin (American journal of emergency medicine, 2014)
Massive posttraumatic bleeding is the leading cause of potentially preventable death among patients with severe trauma. Immediate diagnosis and treatment of traumatic coagulopathy and its differentiation from surgical bleeding after major trauma are critical in the management of such patients. In this case report, we present a 33-year-old woman who had multiple injuries to the head and trunk in motor vehicle collision, resulting in severe bleeding and necessitating emergency surgery. We demonstrate how repeated rotational thromboelastometry and thromboelastography analyses were used to direct the choice of therapy to stabilize her circulatory system for surgery and to differentiate surgical bleed from coagulopathy. Therapy based on massive transfusion protocol and on laboratory coagulation tests would be insufficient to stop bleeding. We conclude that rotational thromboelastometry/thromboelastography analysis plays a critical role in the management of traumatic bleeding and helps us provide more aggressive and targeted therapy for coagulopathy both in the acute and later phases of treatment of severe bleeding.
Keywords: Femoral Fractures; Lung Injury; dospělí; poškození plic; polytrauma; Blood Coagulation Disorders; Female; Adult; tromboelastografie; ženské pohlaví; Multiple Trauma; poranění břicha; krvácení; lidé; Craniocerebral Trauma; Thrombelastography; kraniocerebrální traumata; fraktury femuru; koagulopatie; Hemorrhage; Abdominal Injuries; Humans